Characteristics of off-axis sawteeth with an internal transport barrier in EAST. (9th July 2019) - Xu, Ming; Zhao, H.L.; Zang, Q.; Zhong, G.Q.; Xu, L.Q.; Liu, H.Q.; Chen, W.; Huang, J.; Hu, L.Q.; Xu, G.S.; Gong, X.Z.; Qian, J.P.; et al.
Abstract: An internal transport barrier (ITB) and double tearing modes (DTM) have been observed during the off-axis sawteeth in EAST. The ITB of electron temperature T e is modulated by the sawteeth oscillation, and the formation of an ITB can be divided into three stages: (i) the transport produced by a sawteeth final crash is suppressed at the first stage with a steep gradient of T e ; (ii) the micro-instability is developed at the second stage for further increasing the gradient of T e ; (iii) the ITB is formed eventually after the transition from beta-induced Alfvén eigenmodes (BAEs) to reversed shear Alfvén eigenmodes (RSAEs), where the BAEs-RSAEs pair enables the tracking of directly from the experiment. The off-axis sawteeth final crash is triggered by DTM: (i) the DTM can be excited by the redistribution of the profile of thermal particles, where the downward transport of energetic ions is detected indirectly by the soft x-ray arrays for the first time; (ii) the DTM can be excited by the transformation from the kink instability.